Activation of human neutrophils by dotriacontane from Tynanthus micranthus Corr. Méllo (Bignoniaceae) for the production of superoxide anions - Gomes, Leticia Carneiro; Miguel, Obdulio Gomes; Gasparetto, João Cleverson; Montrucchio, Deise Prehs; Barison, Andersson; Oliveira, Vinícius Bednarczuk; Wunder, Paulo Roberto; Gaspari Dias, Josiane de Fátima; de Oliveira, Letícia Freire; Cansian, Fernanda Colombi; Golin Pacheco, Samanta Daliana; Merino, Francis José Zortéa; et al. (Ciência e Natura, 2022)
The species Tynanthus micranthus Corr. Méllo, is popularly known as "Cipó Cravo" or "Craveiro", and is usually used as a stimulant and aphrodisiac, and found in the north of the State of Paraná - Brazil. The isolate the alkane dotriacontane from T. micranthus and to verify its action on the activation of human neutrophils to produce superoxide anions by the nitroblue tetrazolium reduction method (NBT), in comparison with the activation obtained by commercial dotriacontane. The ethanolic extract dried leaves was prepared by modified Soxhlet apparatus. Then the ethanolic extract was fractionated with n-hexane to obtain the hexane fraction which was submitted to the chromatographic column to obtain the compound dotriacontane. The substance was identified by 1H and 13C NMR spectroscopy. Isolated and commercial dotriacontane were evaluated by the NBT assay for verification of the activation of human neutrophils. The isolated and commercial dotriacontane activated neutrophils (10.0 μg/mL) when compared to phorbol myristate acetate (PMA) (10.0 μg/mL). In the quantitative test commercial dotriacontane induced significant activation when compared to PMA (10.0 μg/mL). The substance dotriacontane, first time identified in the genus Tynanthus. The dotriacontane was shown to be important to confirm the activation of human neutrophils to produce superoxide anions.